Polymorphic variants of the hOGG1, APEX1, XPD, SOD2, and CAT genes involved in DNA repair processes and antioxidant defense and their association with breast cancer risk - А. А. Timofeeva; V. I. Minina; A. V. Torgunakova; О. А. Soboleva; R. А. Тitov; Ya. А. Zakharova; M. L. Bakanova; А. N. Glushkov (Вавиловский журнал генетики и селекции)
Breast cancer is one of the leading causes of mortality among women. The most frequently encountered tumors are luminal tumors. Associations of polymorphisms in the hOGG1 (rs1052133), APEX1 (rs1130409), XPD (rs13181), SOD2 (rs4880), and CAT (rs1001179) genes were studied in 313 nonsmoking postmenopausal patients with luminal B subtype breast cancer. The control group consisted of 233 healthy nonsmoking postmenopausal women. Statistically significant associations of the XPD and APEX1 gene polymorphisms with the risk of developing luminal B Her2- negative subtype of breast cancer were observed in a log-additive inheritance model, while the CAT gene polymorphism showed an association in a dominant inheritance model (OR = 1.41; CI 95 %: 1.08–1.85; Padj.= 0.011; OR = 1.39; CI 95 %: 1.07–1.81; Padj = 0.013 и OR = 1.70; CI 95 %: 1.19–2.43; Padj = 0.004, respectively). In the group of elderly women (aged 60–74 years), an association of the CAT gene polymorphism with the risk of developing luminal B subtype of breast cancer was found in a log-additive inheritance model (OR = 1.87; 95 % CI: 1.22–2.85; Padj = 0.0024). Using MDR analysis, the most optimal statistically significant 3-locus model of gene-gene interactions in the development of luminal B Her2-negative subtype breast cancer was found. MDR analysis also showed a close interaction and mutual enhancement of effects between the APEX1 and SOD2 loci and the independence of the effects of these loci from the CAT locus in the formation of luminal B subtype breast cancer.